Analysis Of Service Quality, Product Quality And Brand On The Decision To Choose Tutoring With Trust As A Mediation Variable - Rica Yulia Nasution; Nurfafrina Siregar; Elfitra Desy Surya (International Journal of Society and Law, 2024)
The purpose of this study is to test and analyze the influence of service quality, product quality, and brand on the decision to choose tutoring with trust as a mediating variable at Genza Education Medan. The method used in this study is associative with a quantitative approach. The sample used in this study was 105 students. The data analysis method in this study used the Structural Equation Model (SEM) with SmartPLS v4.0. The results of this study indicate that: Service Quality has a positive and significant effect on Student Trust, Product Quality has a positive and significant effect on Student Trust, Brand has a positive and significant effect on Student Trust, Service Quality has a positive and significant effect on Student Decisions, Product Quality has a positive and significant effect on Student Decisions, Brand has a positive and significant effect on Student Decisions, Trust has a positive and significant effect on Student Decisions, Service Quality mediated by trust has a positive and significant effect on Student Decisions, Product Quality mediated by trust has a positive and significant effect on Student Decisions, and Brand mediated by trust has a positive and significant effect on Student Decisions. With good service quality, good product quality and a brand embedded in the minds of consumers, it can attract consumer decisions in choosing the services offered, and when consumers have chosen, it means they have trusted the services we offer. Therefore, it is highly recommended that Genza Education always maintain the quality of service, product quality, and maintain the brand in order to gain continuous trust so that students decide to choose to study at Genza Education until they graduate and recommend it to others.